Ketidakseimbangan Elektrolit yang Menyebabkan Fenotipe Brugada: Perpotongan Kompleks antara Hiperkalemia, Hiponatremia, dan Asidosis – Laporan Kasus: Laporan Kasus - Imowanto, Yuddy; Abdullah, Taufiq; Wahyuni, Sri (Cermin Dunia Kedokteran, 2026)
Introduction: Brugada phenocopies (BrP), which are different from real congenital Brugada syndrome (BrS), are clinical entities with different etiology. BrP can manifest in a range of conditions, such as metabolic disturbances like hypokalemia, hyperkalemia, hypophosphatemia, hyponatremia, and acute toxicity. Case: Brugada phenocopy was observed in the ECG of a 68-year-old male, resolved following the correction of hyperkalemia, hyponatremia, and acidosis. The patient presented with septic shock and multiorgan dysfunction, which contributed to severe electrolyte imbalance and metabolic derangements. Despite initial stabilization and improvement in ECG findings after targeted correction, the patient ultimately developed progressive clinical deterioration. Discussion: Recognizing BrP helps identify reversible causes of the ECG changes, allowing for proper treatment and prevention of complications. This case highlights the importance of evaluating underlying metabolic and systemic conditions when encountering Brugada-like ECG patterns. Conclusion: Brugada phenocopy can occur in hyperkalemia and hyponatremia in an acidosis state. Clinicians should consider comprehensive clinical assessment, laboratory evaluation, and ECG monitoring to distinguish BrP from congenital BrS, especially in critically ill patients.